Cranford : return to Cranford [videorecording (DVD)] - Curtis, Simon, 1960-; Dench, Judi, 1934-; Atkins, Eileen, 1934-; Gambon, Michael; Annis, Francesca, 1945-; Staunton, Imelda, 1956-; Wise, Greg, 1966-; Manville, Lesley; Jennings, Alex; Gaskell, Elizabeth Cleghorn, 1810-1865 (BBC Video ; Distributed by BBC Worldwide Americas ; Distributed by Warner Home Video, 2010)
Miss Matty's house is full of life and bustle. Her dream of having a child in the house has been realized in the birth of Tilly, daughter of her maid Martha and carpenter Jem. Elsewhere, the shadow of the railway still looms, but the line has been halted five miles outside Cranford, a disaster as far as Captain Brown is concerned. Meanwhile, as Mr. Buxton returns to town with his son, William, and his niece, Erminia, Miss Matty becomes concerned about another young person, Peggy Bell, who lives in an isolated cottage with her mother and domineering brother. She decides to intervene and engineers an invitation that will bring the four young people together. But when tragedy strikes, she fears she has opened a Pandora's box from which Cranford will never recover.